Secure and Efficient Search over Encrypted Data using Blockchain Technology - Ihab Hamza Ali (International Journal of Computers and Informatics, 2026)
The accelerated popularity of cloud infrastructure and storage has led to a plethora of privacy and security concerns about sensitive data. As a countermeasure, when outsourcing data is usually encrypted. On the other hand, regular encryption makes it impossible to search through that data making any real-world applications challenging. Searchable Symmetric Encryption (SSE) is an efficient building block that allows us to avoid cryptographic search over encrypted data without decryption. However, central SSE systems are subject to single point of failure and transparency. This paper seeks to accomplish secure, efficient and verifiable search over encrypted data by combining SSE with blockchain within a decentralized architecture. The methodology enables data integrity, privacy of queries and the possibility of complete query auditing through meticulous use of smart contracts and distributed ledgers. It implements AES-256-GCM data encryption, HMAC-SHA256 trapdoor generation, Proof of Work blockchain simulation and smart contract execution engine. Experimental results show that it generates indexes for 1,000 documents in less time than 265 ms and executes search in less than 48 Ms per query.
Keywords: Searchable Symmetric Encryption; Blockchain; AES-256-GCM; Smart Contracts; Proof-of-Work; Trapdoor; Privacy-Preserving Search; Distributed Ledger